Research on measurement method of non-synchronous sampling harmonic voltage based on quantum voltage - JIANG Lei; WANG Lei; SHI Zhaomin; WANG Zhijun; XU Suan (Diance yu yibiao)
The programmable Josephson voltage standard (PJVS) has been preliminarily applied to the measurement and analysis of harmonic signals. After overcoming the impact of transition process and Gibbs effect on measurement results, there is still an unavoidable non-synchronous sampling problem. This will introduce large errors in the measurement results and affect the analysis spectrum of the signal. In order to solve above problems, a quadratic weighted Fourier transform method based on quasi-synchronous sampling is proposed. This method combines the improved quasi-synchronous sampling with weighted Fourier transform, and realizes the accurate measurement of harmonic signal through two different weighted and step correction of the original signal. The experimental results show that the standard deviation of harmonic voltage measurement can reach 10-7 magnitude.